Modified titanium implant and preparation method and application thereof
By constructing a tetragonal phase barium titanate and iron-tannin network structure on titanium implants, and using ultrasonic response to produce reactive oxygen species, the problems of acoustic dynamic antibacterial function and biocompatibility in titanium implant scenarios are solved, and effective antibacteriality of common bacteria and good biocompatibility of materials are achieved.
Patent Information
- Application Number
- CN202411831065.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to effectively realize the acoustic antibacterial function in titanium implant scenarios while ensuring good biocompatibility.
By constructing the tetragonal phase barium titanate layer and the iron-tannin network structure layer on the titanium matrix, the ultrasonic response of barium titanate is used to generate reactive oxygen for antibacterial use, and the iron-tannin network improves biocompatibility.
A significant antibacterial effect on Staphylococcus aureus and E. coli under ultrasound conditions was achieved, and the biocompatibility of the material was maintained.
Smart Images

Figure CN119633166A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sonodynamic antibacterial surface modification, and in particular to a modified titanium implant and a preparation method and application thereof. Background Art
[0002] Titanium and titanium alloy medical implants are widely used in bone injury treatment surgeries in orthopedics, dentistry and other fields. However, implant-related infections have brought great burdens and pressures to patients and medical institutions, and their effective prevention and treatment have become one of the urgent problems to be solved in the medical community. Due to the excessive and improper use of antibiotics, bacterial resistance has increased, and traditional antibiotic treatments for implant-related infections have become increasingly difficult to meet the treatment requirements of patients. Studies have shown that piezoelectric materials can promote the production of reactive oxygen species under pressure. Reactive oxygen species have strong oxidizing or reducing properties and can destroy the cell membrane or cell wall of bacteria, causing cytoplasm leakage and killing bacteria. In addition, this pressure is not limited to mechanical pressure. Piezoelectric materials can also be wirelessly activated by external pressure based on ultrasound. Ultrasound is widely accepted in medicine for diagnosis and treatment. Therefore, using ultrasound to trigger piezoelectric materials to promote the production of reactive oxygen species is an emerging sonodynamic antibacterial method.
[0003] Barium titanate has a high piezoelectric coefficient and can be spontaneously polarized. It is a common piezoelectric material and is widely used in the biomedical field. However, the barium titanate currently used in the biomedical field is mainly nanoparticles, and the application scenarios are mainly the antibacterial of wound nanoparticles in vitro and the promotion of bone regeneration and anti-tumor in vivo. Its application in the antibacterial field is still relatively limited. In addition, barium titanate nanomaterials are generally functionalized by methods such as metal doping, but the addition of some metal elements may introduce potential problems of poor biocompatibility. The metal-phenol network is composed of positively charged metal ions and polyphenols, has unique physical and chemical properties, and has great research value in the biomedical field. Among them, tannic acid molecules and iron ions self-assemble to form an iron-tannic acid network structure with good biocompatibility, and its super strong adhesion can form a coating on various surfaces to improve the biological properties of the surface.
[0004] At present, researchers have not yet proposed an effective comprehensive solution to the problems of sonodynamic antibacterial research on titanium implants, the effective combination of barium titanate with specific surfaces, and the biocompatibility of barium titanate materials. Therefore, it is of great research significance and application prospect to study a method with sonodynamic antibacterial function and good biocompatibility for titanium implant scenarios. Summary of the invention
[0005] In order to solve the deficiencies of the above technical solutions, the purpose of the present invention is to provide a modified titanium implant and a preparation method and application thereof.
[0006] The purpose of the present invention is achieved through the following technical solutions.
[0007] A modified titanium implant comprises, from the inside to the outside, a titanium matrix, a tetragonal barium titanate layer and an iron-tannic acid network structure layer.
[0008] In the above technical solution, the titanium substrate is a titanium sheet.
[0009] Another aspect of the present invention also includes a method for preparing the modified titanium implant, comprising the following steps:
[0010] Sodium titanate is used as a seed layer to prepare tetragonal barium titanate on the surface of a titanium matrix, and then an iron-tannic acid network structure is loaded on the surface of the tetragonal barium titanate to obtain a modified titanium implant.
[0011] In the above technical solution, the preparation method of the modified titanium implant specifically comprises the following steps:
[0012] Step 1, grinding and polishing the surface of the titanium substrate, cleaning and drying it, adding it into a sodium hydroxide aqueous solution for hydrothermal reaction, taking it out, repeatedly washing it, and drying it to obtain a titanium substrate with sodium titanate nanocolumns generated on the surface;
[0013] Step 2, adding the titanium substrate with sodium titanate nanocolumns generated on the surface obtained in step 1 into an aqueous solution of barium hydroxide octahydrate for hydrothermal reaction, taking out, repeatedly washing, drying, and high-temperature treatment to obtain a titanium substrate with tetragonal barium titanate attached to the surface;
[0014] Step 3, the titanium substrate with tetragonal barium titanate attached to the surface obtained in step 2 is immersed in a tannic acid aqueous solution and a ferric chloride hexahydrate aqueous solution in turn, and the immersion cycle is repeated for multiple times to load the iron-tannic acid network structure on the surface of the tetragonal barium titanate, and after washing and drying, a modified titanium implant is obtained.
[0015] In the above technical solution, in step 1, the concentration of the sodium hydroxide aqueous solution is 0.5-2 mol / L; preferably, the concentration of the sodium hydroxide aqueous solution is 1 mol / L, the temperature of the hydrothermal reaction is 150-200°C, and the time is 8-12 hours; preferably, the temperature of the hydrothermal reaction is 200°C, and the time is 10 hours.
[0016] In the above technical solution, in step 2, the concentration of the barium hydroxide octahydrate aqueous solution is 0.05-0.1 mol / L; preferably, the concentration of the barium hydroxide octahydrate aqueous solution is 0.05 mol / L; the temperature of the hydrothermal reaction is 100°C, and the time is 12-36 hours; preferably, the time of the hydrothermal reaction is 24 hours.
[0017] In the above technical solution, in step 2, the temperature of the high temperature treatment is 600-1000° C., and the time is 6-12 hours; preferably, the temperature of the high temperature treatment is 800° C., and the time is 10 hours.
[0018] In the above technical solution, in step 3, the mass concentration ratio of the tannic acid aqueous solution to the ferric chloride hexahydrate aqueous solution is 4:1; preferably, the concentration of the tannic acid aqueous solution is 5 mg / mL, the concentration of the ferric chloride hexahydrate aqueous solution is 1.25 mg / mL, and the immersion time is 2 minutes each time, and the cycle is repeated 5 times.
[0019] In the above technical solution, the modified implant has antibacterial properties, piezoelectric properties and biocompatibility.
[0020] Another aspect of the present invention also includes the use of the modified titanium implant as a medical implant, wherein the medical implant is a bone implant and a dental implant.
[0021] The advantages and beneficial effects of the present invention are:
[0022] 1. The present invention uses barium titanate structure and iron-tannic acid network to construct a multifunctional modified titanium implant surface, and uses the active oxygen generated by the ultrasonic response of barium titanate to perform sonodynamic antibacterial. The iron-tannic acid network can improve the biocompatibility of the barium titanate surface and provide more possibilities for multi-pathway antibacterial. The hydrothermal reaction temperature and time of the present invention have a great influence on the nanostructure and crystal structure of sodium titanate. Only the appropriate temperature range and time range can form a relatively uniformly arranged sodium titanate nanostructure. The temperature of high-temperature treatment has a great influence on the crystal structure of barium titanate. Only a specific temperature range can form tetragonal barium titanate, which is a prerequisite for having good ultrasonic response ability. The present invention uses sodium titanate as a seed layer to prepare a tetragonal barium titanate structure on the titanium surface, which has a very important research prospect in the field of implant antibacterial.
[0023] 2. The present invention has excellent antibacterial properties under ultrasonic conditions. Under the excitation of common medical ultrasonic therapeutic instruments, the ultrasonic parameters are 1MHz, 1.5W / cm 2 , 50% duty cycle, and ultrasound for 20 minutes can achieve a significant antibacterial effect on Staphylococcus aureus and Escherichia coli.
[0024] 3. The present invention combines the barium titanate structure with the iron-tannic acid network for the first time, giving the modified titanium implant surface the possibility of multifunctional triggering. The iron-tannic acid network can not only improve the biocompatibility of the modified titanium implant surface, but also enhance the light absorption capacity of the material. Even in future research, it can be considered to use multiple exogenously triggered antibacterial methods.
[0025] 4. The surface of the barium titanate structure of the present invention has more possibilities for metal loading and drug loading. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a scanning electron microscope (SEM) image of the modified titanium implant of Example 1 of the present invention.
[0027] Figure 2 This is a diagram showing the antibacterial effects of each group of Application Example 1 of the present invention on Staphylococcus aureus.
[0028] Figure 3 This is a statistical chart of the antibacterial rate of each group of Application Example 1 of the present invention against Staphylococcus aureus.
[0029] Figure 4 This is a diagram showing the antibacterial effects of each group of Application Example 1 of the present invention on Escherichia coli.
[0030] Figure 5 It is a statistical chart of the antibacterial rate of each group of Application Example 1 of the present invention against Escherichia coli.
[0031] Figure 6 This is the ESR spectrum of hydroxyl radicals generated under ultrasound in Application Example 2 of the present invention.
[0032] Figure 7 This is a diagram showing the results of an in vitro cytotoxicity experiment of an in vitro biological evaluation of Application Example 3 of the present invention. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0034] Example 1
[0035] A method for preparing a modified titanium implant comprises the following steps:
[0036] Step 1, using sandpaper with mesh numbers of 240, 400, 800, 1200, 1500 and 2000 to polish the titanium sheet with both sides having a side length of 1 cm and a thickness of 1 mm, and using an ultrasonic cleaning machine (SB-800D) to ultrasonically clean the polished titanium sheet with anhydrous ethanol and deionized water for 15 minutes, and then drying it for standby use;
[0037] 2.4 g of sodium hydroxide was dissolved in 60 mL of deionized water, stirred at room temperature for 1 hour to obtain a sodium hydroxide aqueous solution, which was then transferred to a metal hydrothermal autoclave equipped with 100 mL of polytetrafluoroethylene lining, and the polished titanium sheet was added. The solution was hydrothermally reacted at 200°C in an oven for 10 hours. After cooling to room temperature, the sample was taken out, washed repeatedly with deionized water and anhydrous ethanol for 3 times, and dried in an air environment at 60°C to obtain a titanium substrate with sodium titanate nanocolumns generated on the surface.
[0038] Step 2, dissolving 0.788g of barium hydroxide octahydrate in 50mL of deionized water, stirring at room temperature for 2 hours to obtain an aqueous solution of barium hydroxide octahydrate with a concentration of 0.05mol / L, and then transferring it to a metal hydrothermal kettle equipped with 100mL of polytetrafluoroethylene lining, adding the titanium substrate with sodium titanate nanocolumns generated on the surface obtained in step 1, and hydrothermally reacting it at 100°C in an oven for 24 hours. After cooling to room temperature, taking out the sample, repeatedly washing it with 0.5mol / L acetic acid, deionized water and anhydrous ethanol for 3 times, drying it in an air environment at 60°C, placing the sample in a porcelain boat, placing it in a muffle furnace, and high-temperature treating it at 800°C for 10 hours. After cooling to room temperature, a titanium substrate with tetragonal barium titanate attached to the surface is obtained.
[0039] Step 3, dissolving 200 mg of tannic acid in 40 mL of deionized water to obtain a tannic acid aqueous solution with a concentration of 5 mg / mL, dissolving 50 mg of ferric chloride hexahydrate in 40 mL of deionized water to obtain ferric chloride hexahydrate with a concentration of 1.25 mg / mL, soaking the titanium substrate with tetragonal barium titanate attached to the surface obtained in step 2 in the tannic acid aqueous solution for 2 minutes, rinsing with deionized water, and then soaking in the ferric chloride hexahydrate aqueous solution for 2 minutes, rinsing with deionized water, repeating the above immersion cycle 5 times, loading the iron-tannic acid network structure on the surface of the tetragonal barium titanate, washing with deionized water, and drying in an air environment at 25°C to obtain a modified titanium implant.
[0040] The modified titanium implant prepared in this embodiment was characterized by SEM, and its microstructure is as follows: Figure 1 shown.
[0041] Example 2
[0042] The modified titanium implant prepared in Example 1 is used as a medical implant, and the medical implant includes bone implants and dental implants, such as hip joint, knee joint and other joint replacement implants, fracture fixation devices, root implants, etc. The following application examples are used to verify its antibacterial properties, piezoelectricity and biocompatibility to illustrate that the modified titanium implant can be used for medical implantation.
[0043] Application Example 1
[0044] The bacterial species in this application example is Staphylococcus aureus or Escherichia coli.
[0045] The in vitro antibacterial property test of the modified titanium implant prepared in Example 1 comprises the following steps:
[0046] Step 1, sterilizing the modified titanium implant of Example 1 by ultraviolet light for 60 minutes.
[0047] Step 2, prepare culture medium: add 10g sodium chloride, 10g peptone, and 5g yeast powder to deionized water to make up to 1L, stir evenly, and sterilize at high temperature and high pressure to obtain culture medium.
[0048] Prepare the culture medium: Fill a 90 mm culture dish with standard Luria-Bertani (LB) medium.
[0049] Step 3, blank group: 1.5×10 7 CFU / mL of Staphylococcus aureus or 1.0×10 7 After the E. coli CFU / mL was diluted 100 times, 20 μL was spread on the culture medium in step 2 and incubated at 37°C for 24 hours.
[0050] Step 4, control group: take 1.5×10 7 CFU / mL of Staphylococcus aureus or 1.0×10 7 10 μL of Escherichia coli with CFU / mL was dropped on the center of the pure titanium sheet surface, left to stand for 20 minutes, and diluted 100 times with the culture medium of step 2. Then 20 μL was spread on the plate in the culture medium of step 2 and incubated at 37°C for 24 hours.
[0051] Step 5, control (ultrasound) group: take 1.5×10 7 CFU / mL of Staphylococcus aureus or 1.0×10 7 10 μL of Escherichia coli with CFU / mL was dripped on the center of the pure titanium sheet surface, and ultrasonic treatment was performed for 20 minutes. After adding the culture solution of step 2 and diluting 100 times, 20 μL was taken to apply to the culture medium of step 2 and incubated at 37°C for 24 hours. The ultrasonic parameters in the ultrasonic treatment were 1 MHz, 1.5 W / cm 2 , 50% duty cycle.
[0052] Step 6, experimental group, take 1.5×10 7 CFU / mL of Staphylococcus aureus or 1.0×10 7 10 μL of Escherichia coli with CFU / mL was dripped on the center of the surface of the modified titanium implant after sterilization in step 1, left to stand for 20 minutes, and diluted 100 times by adding the culture solution in step 2. Then 20 μL was plated in the culture medium in step 2 and incubated at 37°C for 24 hours.
[0053] Step 7, experimental (ultrasound) group, take 1.5×10 7 CFU / mL of Staphylococcus aureus or 1.0×10 710 μL of Escherichia coli with CFU / mL was dripped onto the center of the surface of the modified titanium implant after sterilization in step 1, and ultrasonic treatment was performed for 20 minutes. After adding the culture solution of step 2 and diluting 100 times, 20 μL was taken and coated in the culture medium of step 2, and incubated at 37°C for 24 hours. The ultrasonic parameters in the ultrasonic treatment were 1 MHz, 1.5 W / cm 2 , 50% duty cycle.
[0054] Step 8, recording the temperature during the ultrasonic treatment in steps 5 and 7, and finding that the temperature increased with increasing ultrasonic time. When the test bacteria was Staphylococcus aureus, the temperature eventually stabilized below 55°C, and when the test bacteria was Escherichia coli, the temperature eventually stabilized below 54°C.
[0055] Step 9: Count the number of active bacteria according to the Chinese national standard GB / T 4789.2, and calculate the antibacterial rate of the group in steps (4-7) according to the formula of antibacterial rate = ((AB) / A) × 100%, where A is the number of active bacteria in the group in step 3, and B is the number of active bacteria in the group in steps 4-7. The results are as follows: Figure 2-Figure 5 shown.
[0056] Depend on Figure 2-Figure 3 It can be seen that under ultrasonic conditions, the modified titanium implant has a good antibacterial effect on Staphylococcus aureus, and its antibacterial rate is increased by about 99.51% compared with the blank group.
[0057] Depend on Figure 4-Figure 5 It can be seen that under ultrasonic conditions, the antibacterial rate of the modified titanium implant against Escherichia coli increased by about 97.50% compared with the blank group. Therefore, the modified titanium implant prepared in Example 1 can be used as a medical implant.
[0058] Application Example 2
[0059] The piezoelectric effect principle of the modified titanium implant prepared in Example 1 under ultrasound triggering is verified:
[0060] The principle of ultrasound-triggered piezoelectric effect was verified at the solution level: ultrasound polarized barium titanate, and then the electron-hole pairs separated, causing the oxygen in the solution to gain electrons and transform into superoxide ions, and the water molecules to lose electrons and transform into hydroxyl radicals. The generation of hydroxyl radicals and superoxide ions was tested by using 5,5-dimethyl-1-pyrroline-N-oxide (DMPO) free radical scavenger.
[0061] The specific operation is as follows: when testing hydroxyl radicals, the modified titanium implant is placed in a 100mmol / L DMPO aqueous solution, and after ultrasonic treatment, the solution is transferred to a capillary and detected on an electron spin resonance spectrometer; when testing superoxide ions, the modified titanium implant is placed in a 25mmol / L DMPO methanol solution, and after ultrasonic treatment, the solution is transferred to a capillary and detected on an electron spin resonance spectrometer. The ultrasonic parameters in the above ultrasonic treatment are 1MHz, 1.5W / cm 2 , 50% duty cycle, the result is as follows Figure 6 shown.
[0062] Depend on Figure 6 It can be seen that under the action of ultrasound, the characteristic peak of 1:2:2:1 of hydroxyl radicals was detected in the solution of the modified titanium implant, indicating that the modified titanium implant has good piezoelectric properties. Therefore, the modified titanium implant prepared in Example 1 can be used as a medical implant.
[0063] Application Example 3
[0064] The modified titanium implant prepared in Example 1 was subjected to in vitro biological evaluation.
[0065] The biocompatibility of the modified titanium implants was verified using MC3T3-E1 mouse embryonic osteoblasts. The specific process is as follows:
[0066] MC3T3-E1 mouse embryonic osteoblasts were inoculated in Alpha-MEM medium containing 10% fetal bovine serum and 1% penicillin-streptomycin, and then cultured in a cell culture incubator until the logarithmic growth phase, washed to remove the cells from the wall, and the cell suspension concentration was adjusted to 10,000 cells / mL. 500 μL of cell suspension was added to each well of a 24-well plate. The experiment was divided into three groups: control group, titanium sheet group, and modified titanium implant group, with 3 parallel groups in each group.
[0067] In vitro cytotoxicity experiment: Each experimental group was cultured in a cell culture incubator (5% CO2 and 95% air environment, 37°C) for 3 days. The following operations were all completed under light-proof conditions: remove the surface turbid liquid, add 450 μL of 10% fetal bovine serum and 1% penicillin-streptomycin double-antibody Alpha-MEM culture medium and 50 μL of thiazolyl blue (MTT) solution, and then culture in a cell culture incubator for 4 hours, aspirate the culture medium and MTT solution, add 500 μL of dimethyl sulfoxide (DMSO) solution, and shake on a shaker for 15 minutes. From each experimental group, 100 μL was transferred to a 96-well plate, and then the monochromatic absorbance at 530 nm was measured on an ELISA instrument, and the cell viability of the modified titanium implant group, titanium sheet group and control group was determined based on the absorbance readings. The relative cell viability was calculated by comparing the absorbance values of the modified titanium implant group, titanium sheet group and control group. According to the obtained absorbance data, statistical processing was performed to obtain Figure 7 .Depend on Figure 7 It can be seen that the modified titanium implant group can improve the biocompatibility of the titanium sheet. Therefore, the modified titanium implant prepared in Example 1 can be used as a medical implant.
[0068] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A modified titanium implant, characterized in that: The modified titanium implant comprises a titanium matrix, a tetragonal barium titanate layer and an iron-tannic acid network structure layer from the inside to the outside.
2. The modified titanium implant according to claim 1, characterized in that The titanium substrate is a titanium sheet.
3. The method for preparing the modified titanium implant as claimed in claim 1 or 2, characterized in that: The following steps are involved: Sodium titanate is used as a seed layer to prepare tetragonal barium titanate on the surface of a titanium matrix, and then an iron-tannic acid network structure is loaded on the surface of the tetragonal barium titanate to obtain a modified titanium implant.
4. The preparation method according to claim 3, characterized in that: The specific steps include: Step 1, grinding and polishing the surface of the titanium substrate, cleaning and drying it, adding it into a sodium hydroxide aqueous solution for hydrothermal reaction, taking it out, repeatedly washing it, and drying it to obtain a titanium substrate with sodium titanate nanocolumns generated on the surface; Step 2, adding the titanium substrate with sodium titanate nanocolumns generated on the surface obtained in step 1 into an aqueous solution of barium hydroxide octahydrate for hydrothermal reaction, taking out, repeatedly washing, drying, and high-temperature treatment to obtain a titanium substrate with tetragonal barium titanate attached to the surface; Step 3, the titanium substrate with tetragonal barium titanate attached to the surface obtained in step 2 is immersed in a tannic acid aqueous solution and a ferric chloride hexahydrate aqueous solution in turn, and the immersion cycle is repeated for multiple times to load the iron-tannic acid network structure on the surface of the tetragonal barium titanate, and after washing and drying, a modified titanium implant is obtained.
5. The preparation method according to claim 4, characterized in that: In step 1, the concentration of the sodium hydroxide aqueous solution is 0.5 to 2 mol / L; preferably, the concentration of the sodium hydroxide aqueous solution is 1 mol / L, the temperature of the hydrothermal reaction is 150 to 200° C., and the time is 8 to 12 hours; preferably, the temperature of the hydrothermal reaction is 200° C., and the time is 10 hours.
6. The preparation method according to claim 4, characterized in that: In step 2, the concentration of the barium hydroxide octahydrate aqueous solution is 0.05-0.1 mol / L; preferably, the concentration of the barium hydroxide octahydrate aqueous solution is 0.05 mol / L; the temperature of the hydrothermal reaction is 100° C., and the time is 12-36 hours; preferably, the time of the hydrothermal reaction is 24 hours.
7. The preparation method according to claim 4, characterized in that: In step 2, the temperature of the high temperature treatment is 600-1000° C., and the time is 6-12 hours; preferably, the temperature of the high temperature treatment is 800° C., and the time is 10 hours.
8. The preparation method according to claim 4, characterized in that: In step 3, the mass concentration ratio of the tannic acid aqueous solution to the ferric chloride hexahydrate aqueous solution is 4:1; preferably, the concentration of the tannic acid aqueous solution is 5 mg / mL, the concentration of the ferric chloride hexahydrate aqueous solution is 1.25 mg / mL, and the immersion time is 2 minutes each time, and the cycle is repeated 5 times.
9. The preparation method according to claim 4, characterized in that: The modified implant has antibacterial property, piezoelectric property and biocompatibility.
10. Use of the modified titanium implant as claimed in claim 1 or 2 as a medical implant, characterized in that: The medical implants are bone implants and dental implants.